Understanding Climate Change Perceptions and Attitudes Across Racial/Ethnic Groups. Issue 1 (1st January 2019) - Elias, Troy; Dahmen, Nicole Smith; Morrison, Daniel D.; Morrison, Deborah; Morris, David L.
ABSTRACT: This research uses national survey data from 727 Anglo individuals and 274 Hispanics and African Americans to examine racial differences in pro-environmental inclinations, after controlling for demographic factors. Findings disconfirm conventional wisdom about racial/ethnic minorities being less concerned about environmental and sustainability issues than Anglos. Results demonstrate that racial/ethnic minorities' concerns either surpass or are commensurate with America's racial majority group. The study also examined the direction and strength of the relationship between the multicultural sample's pro-environmental orientations and 5 factors: (a) knowledge; (b) perceived behavioral control and self-efficacy; (c) subjective norms; (d) ideologies; and (e) risk perceptions through the theoretical lens of Maslow's hierarchy of needs. Findings provide implications for public outreach, message design, and multicultural climate change advocacy.